Baroreflex sensitivity in facioscapulohumeral muscular dystrophy. Issue 8 (21st April 2022) - Anselmo, Miguel; Coffman, Shandon; Larson, Mia; Vera, Kathryn; Lee, Emma; McConville, Mary; Kyba, Michael; Keller‐Ross, Manda L.
Abstract: Facioscapulohumeral muscular dystrophy (FSHD), a common form of muscular dystrophy, is caused by a genetic mutation that alters DUX4 gene expression. This mutation contributes to significant skeletal muscle loss. Although it is suggested that cardiac muscle may be spared, people with FSHD have demonstrated autonomic dysregulation. It is unknown if baroreflex function, an important regulator of blood pressure (BP), is impaired in people with FSHD. We examined if baroreflex sensitivity (BRS) is blunted in patients with FSHD. Thirty minutes of resting BP, heart rate, and cardiovagal BRS were measured in 13 patients with FSHD (age: 50 ± 13 years, avg ± SD) and 17 sex‐ and age‐matched controls (age: 47 ± 14 years, p  > 0.05). People with FSHD were less active (Activity Metabolic Index, AMI) (FSHD: 24 ± 30; controls: 222 ± 175 kcal/day; p  < 0.001) but had a similar body mass index compared with controls (FSHD: 27 ± 4; controls: 27 ± 4 kg/m 2 ; p  > 0.05). BRSup (hypertensive response), BRSdown (hypotensive response), and total BRS were similar between groups (BRSup: FSHD: 12 ± 8; controls: 12 ± 5 ms/mmHg; BRSdown: FSHD: 10 ± 4; controls: 13 ± 6 ms/mmHg; BRS: FSHD: 14 ± 9; controls: 13 ± 6 ms/mmHg; p  > 0.05). Mean arterial pressure was similar between groups (FSHD: 96 ± 7; controls: 91 ± 6mmHg). Individuals with FSHD had an elevated heart rate compared with controls (FSHD: 65 ± 8; controls: 59 ± 8 BPM; p  = 0.03), but when co‐varied for AMI, this relationship disappeared ( p  = 0.39). These findings suggest that BRS is not attenuated in people with FSHD, but an elevated heart rate may be due to low physical activity levels, a potential consequence of limited mobility. Abstract : The current study provides evidence that baroreflex and heart rate variability in individuals with FSHD are preserved, despite their lower physical ability indicated by the FSHD‐health index. Further, our observations suggest that an elevated heart rate in FSHD may be indicative of physical inactivity or deconditioning, which may put this group at risk for future CVD or cardiac events, but this appears to be secondary to FSHD or overexpression of the DUX4 gene mutation, as we did not observe alterations in autonomic function in this group.